Evaluación de treinta y cuatro variedades de maní mediante técnicas multivariadas (1983)
Thirty four cultivated entries of peanut were grown during 1.979 at the Centro Experimental Nataima and Ia Hacienda Bledonia in a randomized coinplete block design with three replications at each location. Thirty one characters from distinct parts of the plant were recorded. From the combined analysis of variance, the coefficient r = &.$.- /( -Q' was estimated. Based upon this coefficient it was found that those characters which were least affected by the enviroment corresponded to the reproductive characters and the converse was true for the vegetative characters. Principal component analysis, based upon the correlation matrix, showed that 74% of the total variation was explained by the first four characteristic values. The first characteristic vector can be considered, at least in part, a vector of pod development because length and width are indicators of growth; the first vector was also related with yield. The dendogram also indicated great diversity among the 34 entries and those can be considered of immense value for future breeding programs.